Relación de los estilos parentales en las áreas de la inteligencia emocional de niños y niñas de grado sexto de una Institución educativa pública de Roldanillo Valle. (2023)
The development of children is a subject of study of great importance for the discipline of psychology, for three main reasons: 1) the responsibility of the community, State and family to guarantee their integral care, 2) they represent the future of society and 3) at this stage the biopsychosocial bases are established that will mark a large part of the process of thinking, feeling and acting of the individual. In this sense, this research intends to make relevant contributions to the topic in question by establishing the relationship of parental styles in the areas of emotional intelligence of boys and girls of 11 and 12 years old in sixth grade of the educational institution Nuestra Señora de Chiquinquirá in Roldanillo-Valle del Cauca, based on the parental styles proposed by Darling and Steinberg, and on the model of emotional intelligence ability proposed by Salovey and Mayer